Global warming [ the signs and the science - Kennard, David; Mason, Scott; Morissette, Alanis (Distributed by PBS Home Video, 2005)
This documentary profiles people who are living with the grave consequences of a changing climate, as well as the individuals, communities and scientists inventing new approaches to safeguard our children's future. Filmed across the U.S., Asia and South America, this program brings the reality of climate change to life and offers viewers a variety of ways to make a difference in their own communities